Patriarcado e teoria política feminista: possibilidades na ciência política - Bruna Camilo de Souza Lima e Silva (2019)
This Master thesis presents a research on the concept of patriarchy in Political Science, considering the different paths that it traverses through the different feminist perspectives. The objective of this research is to find, in Feminist Political Theory, the possibilities and implications of the concept of patriarchy in Political Science. The central hypothesis is that a greater centrality in the political dimension of patriarchy in its institution and reproduction of political power makes it a more consistent and interpellant operator of contemporary democratic theories. In this thesis, a brief analysis is performed on the number of papers published in well-qualified Brazilian academic journals, in order to prove that the themes surrounding the concept of patriarchy are still insufficient and with little visibility. It is evident that Political Science has patriarchy among its conceptual structures, which precludes the deconstruction of paradigms that are embedded and incompatible with feminisms. The first effort was precisely to address the concept of patriarchy in feminisms, centering on the production and reproduction of political power as the way in which it focuses on all dimensions of social life. From the work of the concept and through feminist marxist theorists, this research approaches the economic question of patriarchy and its implications, presenting perspectives still very little studied. With a feminist approach, this thesis seeks to build a concept of possible patriarchy in Political Theory, which contributes to existing feminist studies. In order to show the conceptual implications of patriarchy, this research also aims to address, in an initial way, contemporary canonical democratic theories based on feminist criticism. It will theoretically examine some categories, such as "violence," "women's autonomy," "reproduction of social life”, and "underrepresentation", that make it possible to measure how patriarchal a democratic state can be.